Indigenous cattle breeds and factors enhancing their variation, potential challenges of intensification and threats to genetic diversity in Uganda. (16th December 2015) - Kabi, Fredrick; Muwanika, Vincent; Masembe, Charles
Summary: Indigenous cattle support approximately 26.1 percent of Ugandan families through provision of food and income in addition to the supply of socio-cultural wealth and security. Cattle keepers have developed and maintained variations of indigenous cattle phenotypes and genotypes suited to their agro-ecological zones through traditional management practices and socio-cultural aspects. The Ankole ( Bos taurus indicus ), East African shorthorn Zebu ( Bos indicus ) and their crossbred cattle constitute the main indigenous breeds, adding up to 93.3 percent of the Ugandan herd. With intensions to increase productivity, state policies encourage livestock farmers to upgrade local genotypes towards high yielding exotic dairy cattle. This if not appropriately planned is likely to result into loss of local genetic diversity, well endowed with resilience to local climatic conditions, endemic diseases and feed resource constraints. Here in, we review literature related to indigenous cattle in Uganda including how diverse landscapes, local management practices and socio-cultural aspects have enriched patterns of indigenous cattle variations. Then we highlight potential challenges of intensive management, increased selection for higher productivity and threats to genetic diversity of indigenous cattle populations. Since indigenous cattle vary with landscapes and socio-cultural values, have taken decades to establish, efforts to save them through genetic diversity studies, conservation and farmers sensitization should be undertaken immediately. Résumé: Les bovins indigènes se soutiennent environ 26.1% des familles ougandaises par la fourniture de nourriture et de revenus, en plus de la fourniture de la richesse et de la sécurité socio-culturelle. Les éleveurs de bovins ont développé et maintenu variations de phénotypes et les génotypes de bovins indigènes adaptées à leurs zones agro-écologiques (ZAE) grâce à des pratiques de gestion traditionnelles et les aspects socio – culturels. Le Ankole (Bos taurus indicus), shorthorn Afrique de l'Est Zébu (EASZ) (Bos indicus) et leurs hybrides constituent les principales races de bovins indigènes, en ajoutant jusqu'à 93.3% du troupeau ougandaise. Avec intensions pour augmenter la productivité, les politiques de l'Etat encouragent les éleveurs à améliorer génotypes locaux vers les bovins élevés laitiers exotiques rendement. Cette si pas prévu de manière appropriée est susceptible d'entraîner dans la perte de la diversité génétique locale, bien dotée en la résilience aux conditions climatiques locales, les maladies endémiques et les contraintes de ressources d'alimentation. Ici, dans, nous passons en revue la littérature liée aux bovins indigènes en Ouganda, y compris la façon dont divers paysages, pratiques de gestion locales et les aspects socio- culturels ont renforcé types de variations de bovins indigènes. Ensuite, nous mettons en évidence les défis potentiels de la gestion intensive, une sélection accrue pour une meilleure productivité et des menaces à la diversité génétique des populations de bovins indigènes. Depuis les bovins indigènes varient avec des paysages et des valeurs socio-culturelles, ont pris des décennies à établir, les efforts pour les sauver à travers des études de la diversité génétique, la conservation et la sensibilisation des agriculteurs doivent être prises immédiatement. Resumen: El ganado bovino autóctono sostiene a, aproximadamente, el 26.1 por ciento de las familias ugandesas mediante el abastecimiento en alimentos y el aporte de ingresos, además de por su importancia sociocultural en términos de riqueza y seguridad. Los criadores de ganado bovino autóctono han desarrollado y mantenido variaciones en el fenotipo y en el genotipo del ganado, que se adecúan a sus zonas agroecológicas, por medio de las prácticas tradicionales de manejo y por influencia de aspectos socioculturales. El ganado Ankole ( Bos taurus indicus ), el Cebú de Cuernos Cortos del Este de África (EASZ por sus siglas en inglés, Bos indicus ) y sus cruces constituyen las principales razas autóctonas, llegando a representar hasta el 93.3 por ciento de la cabaña ugandesa. Con la intención de incrementar la productividad, las políticas estatales animan a los ganaderos a mejorar los genotipos locales con la vista puesta en el ganado lechero exótico de alta producción. Esto, si no se planifica adecuadamente, puede fácilmente llevar a una pérdida de la diversidad genética local, bien dotada de resistencia a las condiciones climáticas locales, a las enfermedades endémicas y a las limitaciones en la alimentación. En este artículo, revisamos la documentación existente sobre el ganado bovino autóctono de Uganda, incluido cómo diferentes entornos, prácticas locales de manejo y aspectos socioculturales han generado patrones de variación en el ganado bovino autóctono. A continuación, hacemos hincapié en los desafíos que pueden derivar del manejo intensivo, de una mayor selección para incrementar la productividad y de las amenazas a la diversidad genética de las poblaciones bovinas autóctonas. Dado que han sido necesarias décadas para que surgieran en el ganado bovino autóctono las variaciones debidas al entorno y a los valores socioculturales, los esfuerzos necesarios para preservarlas deben iniciarse cuanto antes (estudios de diversidad genética, proyectos de conservación y la sensibilización de los ganaderos).